Public school catering's role in the transition towards a sustainable food system - Stolt, Linnea (2020)
Public catering can have a considerable environmental and educational impact. A scenario of more legume and less meat consumption in Sweden was in the present study used as a tool to explore the possibilities of Swedish public school meals to become more sustainable. Strong structuration theory provided a focus on organisational structure and stakeholder influence, enabling a holistic view of the issue at hand. A literature review, on the topics of successful implementation of sustainability projects within public catering and individual agency within school meals, provided a knowledge base from which an online survey and a guide for complementary interviews were built. The survey was aimed at municipal dietary managers and assessed their experiences of working with sustainable school meals and their attitudes towards the dietary scenario. Furthermore, the survey tried out a way of measuring how much legumes and meat are served in school canteens. The complementary interviews focused on individual actors' perceived agency to act for sustainable change. The results suggest that the study participants in general have both the knowledge and interest to make school meals more sustainable. They also saw the more legumes dietary scenario as desirable. Complicating factors are that the priorities of catering organisations and schools are often not well aligned, and resources are lacking to work on collaborations to improve this. It is also often unclear who has the responsibility to make sure teaching on sustainability is carried over from the classroom to the canteen. Individual agents with a high motivation to make positive change can be important drivers of sustainability projects, but for a change such as significantly greener school meals to take place, a whole food culture needs to change. Educational efforts and finding ways of engaging multiple stakeholders in the decisions are needed to this end. Unambiguous political goals, with adequate action plans, would give structure to the work on more sustainable school meals. Finding ways of quantifying and comparing sustainability efforts between municipalities would draw attention to the importance of the matter. The approach that was tried out in the present study however proved to be too impractical to use.